Assessment of risk of diabetes by using Indian Diabetic risk score (IDRS) in Indian population. (April 2020) - Nagarathna, Raghuram; Tyagi, Rahul; Battu, Priya; Singh, Amit; Anand, Akshay; Nagendra, Hongasandra Ramarao
Abstract: Aims: To screen the Indian population for Type 2 Diabetes Mellitus (DM) based on Indian Diabetes Risk Score. Our main question was; Does Indian Diabetic risk score (IDRS) effectively screen diabetic subjects in Indian population? Methods: Multi-centric nationwide screening for DM and its risk in all populous states and Union territories of India in 2017. It is the first pan India DM screening study conducted on 240, 000 subjects in a short period of 3 months based on IDRS. This was a stratified translational research study in randomly selected cluster populations from all zones of rural and urban India. Two non-modifiable (age, family history) and two modifiable (waist circumference & physical activity) were used to obtain the score. High, moderate and low risk groups were selected based on scores. Results: In this study 40.9% subjects were detected to be high risk, known or newly diagnosed DM subjects in urban and rural regions. IDRS could detect 78.1% known diabetic subjects as high risk group. Age group 50–59 (17.4%); 60–69 (22%); 70–79 (22.8%); >80 (19.2%) revealed high percentage of subjects. ROC was found to be 0.763 at CI 95% of 0.761–0.765 with statistical significance of p < 0.0001. At >50 cut off, youden index showed the sensitivity of 78.05 and specificity of 62.68. Regression analysis revealed that IDRS and Diabetes are significantly positively associated. Conclusions: Data reveals that IDRS is a good indicator of high risk diabetic subjects.